LEVEL OF EFFICIENCY AND FEASIBILITY OF BUSINESS RAREING QUAIL EGG FEEDING A COMBINATION OF HOUSEHOLD ORGANIC WASTE AND FRESH MAGOTS - Pala, Fransiskus Yeheskiel; Darmawan, Hariadi; Suroto, Karunia Setyowati (Universitas Veteran Bangun Nusantara, 2025)
The financial feasibility analysis was carried out to determine the financial feasibility of the quail egg farming business. This study aims to obtain a calculation of the financial feasibility analysis of quail egg cultivation business fertilized with household organic waste and fresh mogots. The aspects of financial feasibility analysis calculated in this study include HPP, BEP, R/C Ratio, NPV, IRR and PP. The results of the financial feasibility analysis showed: (a) cost of production (HPP) of Rp 26.7882; (b) selling price of IDR 27,000/kg; (c) BEP unit 5,948 and BEP price IDR 217,066,163; (d) NPV with a positive value of Rp 5,107.37; (e) IRR NPV positive 1 is and NPV 701. 287, and NPV positive 2 is 696,011 which indicates a higher figure compared to the bank interest rate which is 212%; (f) R/C Ratio 1.24; (g) The payback period is shorter than the project life, i.e. 1 year, 5 months and 1 day.